1998
DOI: 10.1098/rspb.1998.0529
|View full text |Cite
|
Sign up to set email alerts
|

Resistance management: the stable zone strategy

Abstract: The di¡erent strategies of insecticide resistance management that have been formulated so far consist of delaying the appearance and spread of resistance genes. In this paper, we propose a strategy that can be used even if resistance genes are already present. This strategy consists of applying insecticides in an area smaller than a certain critical size, so that gene £ow from the untreated area, combined with the ¢tness cost of the resistance genes, prevents its frequency reaching high equilibrium value. A tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 33 publications
3
133
0
Order By: Relevance
“…However, the above results call for monitoring programmes aimed at assessing periodically the level of susceptibility of individual populations to these compounds, as well as implementing insecticide rotation, integrated control and/or other strategies (e.g. Lenormand & Raymond 1998) to maintain the efficacy of the compounds themselves.…”
Section: Discussionmentioning
confidence: 99%
“…However, the above results call for monitoring programmes aimed at assessing periodically the level of susceptibility of individual populations to these compounds, as well as implementing insecticide rotation, integrated control and/or other strategies (e.g. Lenormand & Raymond 1998) to maintain the efficacy of the compounds themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Reversion to susceptibility may be closely linked to the strength of resistance costs and to the rate of immigration of susceptible individuals into the treated area (Tabashnik and Croft, 1982;Carrière and Tabashnik, 2001). Lenormand and Raymond (1998) described a management model leading to the confinement of the resistance genes, by the use of fluctuating intensities of both gene flow and selection (for and against resistance). In south-eastern France apple orchards, the mean frequency of resistance was close to 75% according to recent field collections (Sauphanor et al, 2000).…”
Section: Pleiotropic Costs and Resistance Managementmentioning
confidence: 99%
“…Indeed, if resistance entails a fitness cost, the spread of a recessive allele could be prevented by an appropriate resistance management strategy (Lenormand and Raymond, 1998;Carrière and Tabashnik, 2001;Carrière et al, 2004;Bates et al, 2005). Although fitness costs associated with Bt resistance were not always detected (eg Gould and Anderson, 1991;Tang et al 1997), they have been reported in many pests (Groeters et al, 1994;Trisyono and Whalon, 1997;Alyokhin and Ferro, 1999;Oppert et al, 2000;Carrière et al, 2001a, b;Akhurst et al, 2003;Janmaat and Myers, 2003;Higginson et al, 2005.…”
Section: Introductionmentioning
confidence: 99%